Ascending-to-Descending Bypass for Simultaneous Surgery of Aortic Coarctation with Other Cardiac Pathologies - Reents, W.; Froehner, S.; Diegeler, A.; Urbanski, P. P. (The Thoracic and Cardiovascular Surgeon, 2012)
Background The appropriate approach for aortic coarctation associated with other cardiac diseases necessitating surgery is still controversial. The aim of this study was to evaluate the results after simultaneous surgery performed via median sternotomy and consisting of extra-anatomical ascending-to-descending aortic bypass and various other cardiac procedures.Methods Between January 1999 and February 2009, 13 consecutive patients with aortic coarctation coexistent with other cardiac diseases necessitating surgery underwent simultaneous surgery via median sternotomy. An extra-anatomical ascending-to-descending aortic bypass for coarctation repair was performed in all patients accompanied by various cardiac procedures (5 aortic root and valve replacement; 2 aortic valve replacement; 2 coronary artery bypass grafting; 2 mitral valve repair; 1 aortic valve replacement and coronary artery bypass grafting; 1 mitral and tricuspid valve repair). There were 3 women and 10 men with a mean age of 52 years (range 25–69). Two patients had recurrent or residual coarctation 37 and 46 years after previous surgical repair, respectively.Results Early mortality was 0 and there was only 1 late death during the follow-up of up to 11 years. New York Heart Association (NYHA) functional class improved on average from 2.4 to 1.2. At the last follow-up, blood pressure measured at the upper and lower extremities showed no gradient in any patient, indicating a durable function of the extra-anatomical bypass. Only 3 patients were on reduced antihypertensive therapy; 8 patients were on the same medication and 1 patient required increased medication therapy compared with the medication prior to surgery.Conclusions Ascending-to-descending bypass can be performed via median sternotomy simultaneously with various cardiac procedures without considerable extension of the procedure. The operative and long-term results are excellent, and this approach can be recommended as the procedure of choice in patients with aortic coarctation and additional cardiac diseases necessitating surgery.
Keywords: aorta/aortic; cardiac; surgery/incisions